Study of Histomorphological Patterns of Uterine Leiomyomas: An Observational Study - Archana Tiwari; Pratima Sapkota (Journal of Nepal Medical Association)
Introduction: Uterine leiomyoma, also known as a fibroid, is a benign mesenchymal tumor derived from the smooth muscle of the uterus. It is the most common tumor in women with an estimated incidence of 20%-40% in women during their reproductive years. Leiomyoma can occur in any organ, but the most common forms appear in the uterus. This study is conducted to analyze histomorphological patterns of uterine leiomyomas. Methods: An observational cross-section was conducted between 1st June 2021 and 31st May 2023 in the Department of Pathology of a Medical College and Teaching Hospital. Patients with leiomyoma were included in the study. Clinical, sonographic, gross, and histopathology findings were analyzed. Ethical approval for the study was obtained from Institutional Review Committee (Reference Number: LMC10/B-021). Results: There were 100 patients with leiomyoma during the study period, among whom 55 (55%) were 40-49 years old. There were 65 (65%) patients in the group with a parity of two to three. Abnormal uterine bleeding was observed in 60 (60%) of the cases. Histologically 84 (84%) of the cases were simple conventional leiomyoma. The co-existing conditions found were cystic ovarian disease 37 (37%), adenomyosis 19 (19%), and cervical intraepithelial neoplasia 12 (12%). Conclusions: Conventional leiomyoma is the commonest histological subtype and and the most common clinical presentation is abnormal uterine bleeding.